Pengelolahan Sampah Di Kawasan Wisata Bukit Kebo Balikpapan Melalui Konsep Bank Sampah - Sulaiman, Mochamad; Christopher Davito Prabandewa Hertadi; Sigit Rahmat Rizalmi; Andaya Rizky Trisambada; Achmad Riyadi; Samara Putri Salman (Fakultas Teknik, Universitas PGRI Banyuwangi, 2024)
The ecotourism environment must be kept clean and sustainable for the sake of sustainability and comfort of visitors. Bukit Kebo Tourism Area is one of the many ecotourism and edutourism destinations in Balikpapan City. With the increasing number of visitors (tourists) to Bukit Kebo, it has an impact on the increase in the volume of waste produced. The increase in the volume of waste has not been managed properly, because the waste is only piled up and burned. Where the impact of hoarding can provide the potential for environmental pollution and the results of burning waste also cause pollution. In overcoming these problems, a solution is offered by using the concept of a waste bank to manage waste, as well as providing assistance to partners about the importance of recycling waste. In addition, education is also carried out for visitors to increase awareness and attention about the importance of maintaining environmental cleanliness through the installation of appeal plaques and campaigns through the distribution of brochures. The results of the responses given by management partners and visitors show quite positive results regarding the impacts given from the results of activities to always maintain environmental sustainability and cleanliness, especially in tourist areas.